Karakteristik Prasarana dan Sarana Perumahan Suku Kamoro di Kampung Hiripau Distrik Mimika Timur Kabupaten Mimika - Junita Saputri; Deasy Widsyastomo; Juliani Wairata (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2025)
Hiripau Village, inhabited by the Kamoro ethnic community, exhibits housing conditions that do not meet the basic infrastructure standards for livable settlements. This study aims to identify the characteristics of housing facilities and infrastructure, as well as to formulate a development strategy for the area. A qualitative descriptive method was employed, utilizing field observation, in-depth interviews with local residents and traditional leaders, and documentation of existing conditions. The findings indicate that basic infrastructure components such as neighborhood roads, clean water supply, sanitation systems, drainage, and waste management are in inadequate condition. Therefore, the study recommends an integrated planning approach for infrastructure improvement, emphasizing active community participation in the management and maintenance of the residential environment to achieve a habitable and sustainable settlement.